Clinical Profile of Meningitis in Children - Uddin, MB; Rahman, M; Jahan, KI; Yeasmin, S; Rahman, F (TAJ: Journal of Teachers Association, 2018)
Meningitis is an emergency clinical problem in pediatrics. The mortality from meningitis is close to 100% in untreated individuals and can still be up to 40% in children who received appropriate antibiotic therapy in developing countries. A cross sectional study was done to address the common presentation of meningitis among the children. The study was conducted in the Pediatric unit of Rajshahi Medical College Hospital from March 2008 to July 2009. A total of 130 suspected case of meningitis patients were included in the study. Among them 102 were diagnosed as meningitis of 66 children with pyogenic meningitis, 36 children with aseptic meningitis and 28 children without meningitis were taken as non meningitis group. This study showed that all patients (100%) had fever. 97 (95.10%) had symptom of convulsion. Vomiting was present in 62 (60.78%), excessive cry or irritability present in 50(49%) cases. This study expressed that 75 (73.53%) patients had bulged fontanel. Neck rigidity was present in 67 (65.69%). Only 32.35% had kernig’s sign positive and 17.65% present with Brudginsky’s sign positive. The infancy was the most vulnerable age for pyogenic meningitis. H. influenzae were the leading pathogen (24.24%) in infancy followed by S. pneumoniae (21.21%). The result shows that among 66 pyogenic meningitis, 26 (39.39%) were completely cured and 24 (36.37%) were cured with sequelae. Out of 36 aseptic meningitis 27 (75.00%) were completely cure. TAJ 2015; 28(1): 6-11